When prevention is the best remedy: HIV pre-exposure prophylaxis (PrEP) among adolescents gays and transgender women in Belo Horizonte, Minas Gerais State, Brazil - Érica Dumont Pena; Mateus Rodrigues Westin; Maria José Duarte; Marília Greco; Ana Paula Silva; Yuppiel Franmil Martinez; Unaí Tupinambás; Dirceu Bartolomeu Greco (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2023)
Based on the incorporation of pre-exposure prophylaxis (PrEP) as an HIV prevention strategy and considering the need to comprehend the use of medication among young people, this article analyzes narratives of gay men and transgender women from Belo Horizonte, Minas Gerais State, Brazil, participating in the PrEP1519 study. This is a qualitative research, based on the interpretative anthropology, developed by 10 in-depth interviews with PrEP users followed-up for at least three months between October and November 2019. The results showed that the drug was seen as the main motivation for participating in the study and as a strategy combined with the use of condoms, whether as additional prevention, or assuming the leading role. The medication revealed signs built by the gender performances and their relation to other medications, especially the experience of trans girls in hormonal therapy. Regarding the socialization of the use of PrEP, the narratives showed that there was no secret between the couples, which did not meant that stigmas on the association with HIV did not exist, mainly in the virtual context. In the family environment, they reported questions about the preventive function of the medication and the voluntary nature of the participation in the study. The youth's narratives revealed plural meanings of the medication and its social use, composing both the boys' and girls' performances. The signs attributed to the medication indicated that in addition to maintenance of health, the medication improves life and sexual freedom.